SIMULATION MODELING OF THE PULSE WAVE DURING PHYSICAL LOAD AS A MEANS OF VERIFYING SIGNAL PROCESSING METHODS - KHVOSTIVSKYI, MYKOLA; UNIIAT, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents a mathematical and simulation model of the human pulse signal during physical load, which can be used to verify digital signal processing methods in biomedical applications. The relevance of the research arises from the need to develop controlled models that reproduce physiologically consistent cardiovascular dynamics without the necessity of complex experimental procedures. The proposed approach integrates parametric modeling of heart rate variability, temporal discretization of observation, and morphological synthesis of pulse waves by convolving discrete cardiac impulses with a vascular response kernel. The model is implemented in the MATLAB environment, enabling numerical experiments, parameter variation, and simulation of different physiological conditions ranging from rest to active workload. Heart rate dynamics are described by a piecewise-smooth function that includes rest, acceleration, steady-load, and recovery phases with continuous transitions corresponding to the real physiological adaptation of the cardiovascular system. Cardiac beats are simulated through phase integration of the instantaneous frequency, where each crossing of an integer phase value denotes a new cardiac impulse. The morphology of the pulse wave is modeled as a superposition of forward and reflected components, whose amplitudes, delays, and asymmetry determine the characteristic dual-peaked shape typical of pulse signals. This allows the model to reproduce waveform transformations under varying load conditions. The resulting signal is physiologically plausible, parameter-controlled, and suitable for verifying algorithms of peak detection, filtering, adaptive segmentation, and heart rate variability (HRV) analysis. The model demonstrates high reproducibility, stability, and simplicity of implementation. Using simulation modeling as a verification tool reduces dependence on real clinical experiments and provides standardized conditions for testing digital signal processing techniques. The proposed work contributes to the development of bioengineering models of cardiovascular dynamics and to the enhancement of intelligent monitoring systems for human physiological parameters. У статті представлено математичну та імітаційну модель пульсового сигналу людини під час фізичного навантаження, що може бути використана для верифікації методів цифрової обробки біомедичних сигналів. Актуальність роботи зумовлена потребою у створенні контрольованих моделей, які дозволяють відтворювати фізіологічно обґрунтовану динаміку серцево-судинної системи без проведення складних експериментів. Запропоновано підхід, який поєднує параметричне моделювання частоти серцевих скорочень, часову дискретизацію процесу спостереження та морфологічне формування пульсових хвиль шляхом згортки окремих серцевих імпульсів із ядром судинної відповіді. Модель реалізовано у середовищі MATLAB, що забезпечує можливість чисельного експерименту, варіації параметрів навантаження та відтворення різних фізіологічних станів організму. Частота серцевих скорочень у моделі описується кусково-гладкою функцією, що включає фази спокою, наростання, стабільного навантаження та відновлення, із плавними переходами між ними, що відповідає реальній реакції серцево-судинної системи. Імітація серцевих ударів базується на інтегруванні миттєвої частоти для формування фазової змінної, моменти переходу якої через цілі значення визначають появу окремих серцевих імпульсів. Морфологія пульсової хвилі формується як суперпозиція прямої та відбитої компонент, параметри яких контролюють амплітуду, затримку та асиметрію сигналу. Такий підхід дозволяє відтворити характерну форму пульсового сигналу, а також моделювати її зміну під дією навантаження. Отриманий сигнал є фізіологічно достовірним, має контрольовані параметри і придатний для перевірки алгоритмів виявлення піків, фільтрації, адаптивної сегментації та оцінювання варіабельності серцевого ритму (HRV). Модель відзначається простотою реалізації, стабільністю та високою відтворюваністю результатів. Використання імітаційного моделювання як засобу верифікації дозволяє зменшити потребу в реальних клінічних експериментах, забезпечуючи стандартизовані умови для тестування методів цифрової обробки. Представлена робота створює підґрунтя для подальшого розвитку біоінженерних моделей серцево-судинної динаміки та вдосконалення інтелектуальних систем моніторингу фізіологічних параметрів людини.